Design of devices and systems - Middendorf, William H. (Marcel Dekker, 1986)
This book introduction the concept of the life cycle a product in the first chaper along with a six - step design process that seems to fit most products well. The need for safe product that truly the needs of the intended purchaser is emphasized throughout the book.